Pharmacovigilance Program: Malaysia Versus Nigeria, An Update - Mainul, Haque; Abdullahi Rabiu, Abubakar (Association of Indian Pharmacist, 2016)
Spontaneous reporting and intensive monitoring are the conventional systems used for detecting, recording and reporting adverse drug reactions. Using spontaneous reporting a lot of successes was made as existing adverse drug reactions were identified and new ones were prevented. In general, regulatory authorities consider only the information and outcome of the premarketing clinical trial in controlled settings to approve and register a drug for human use. As such, not much is known about the drug beyond the data obtained from clinical trials in controlled settings. The outcome of pre-marketing studies for safety, efficacy, and quality of new medicines will not represent the whole population of patients that will use the drugs when they are approved. Henceforth, suitable and constant post-marketing surveillance (PMS) is indispensable. The two types of post-marketing studies are descriptive and analytical. Descriptive study is carried out to generate adverse drug reaction signals (hypotheses) while the analytical study is done to test hypotheses and determine associations or causal relations between observed effects and particular drugs. Examples of descriptive studies are spontaneous reporting and intensive monitoring while analytical studies include case-control studies, cohort studies, and post-marketing clinical trials. The aim of this review is to highlight the menace of adverse drug reactions, challenges of the spontaneous reporting system and, more importantly, the information available from Malaysia and Nigeria.